Hot‐cracking susceptibility of fully austenitic stainless steel using pulsed‐current gas tungsten arc‐welding process. Issue 3 (19th October 2020) - Abu‐Aesh, Mohamed; Taha, Mohamed; El‐Sabbagh, Ahmed Salem; Dorn, Lutz
Abstract: The pulsed‐current gas tungsten arc‐welding process (PCGTAW) has recently been recommended as an approach to eliminate the high susceptibility of austenitic stainless steel to hot cracking. Within a wide range of variables, in the present study, the effects of pulse frequency, time ratio, and pulse current on the cracking susceptibility of austenitic stainless‐steel thin sheets are investigated. A fan‐shaped cracking test specimen is adopted, and suitable final dimensions are obtained by conducting some preliminary experiments. A good correlation is found between the maximum crack length, which is taken as a cracking susceptibility index, and the pulse form variables. The results are found to be significantly improved when compared with those of the continuous‐current process, which indicates that the PCGTAW process has an effective role in reducing the hot‐cracking susceptibility. The optimal conditions of the pulse form variables based on the hot‐cracking susceptibility are determined. The optimal values of the time ratio are found to be less than 50%, together with a pulse frequency of less than 1 Hz. Some new microstructure measures, such as columnar structure ratio, grain orientation angle, puddle diversion angle, and overlapping ratio, which are originally defined in this work, in addition to grain size and puddle form factor (aspect ratio), are used to interpret the hot‐cracking behavior. All are found to have a direct impact on the hot‐cracking susceptibility. The results obtained from microstructure examinations showed that the cracks formed are either intergranular or transgranular cracks. Abstract : In the present study, the effects of pulse frequency, time ratio, and pulse current on the cracking susceptibility of austenitic stainless steel thin sheets are investigated. A fan‐shaped cracking test specimen is adopted, and suitable final dimensions are obtained by conducting some preliminary experiments. The results are found to be significantly improved when compared with those of the continuous‐current process, indicating that the pulsed‐current gas tungsten arc‐welding process (PCGTAW) has an effective role in reducing the hot‐cracking susceptibility.